PEMBERDAYAAN KELUARGA DAN MASYARAKAT MELALUI OPTIMALISASI TUGAS KESEHATAN KELUARGA TERHADAP PERAWATAN TB PARU - Marwansyah, Marwansyah; Zainab; Farhat, Yasir; Annisa, Farah; Rahman, Arief; Azhima, Rizkan (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
The Karang Intan 2 Health Center area is one of the health centers where the number of pulmonary TB sufferers is still quite high; recorded in 2022, 29 patients were found and are currently undergoing a treatment program. There were 14 new cases added from January to April 2023; this shows that the transmission of pulmonary TB in the community is still quite high even though the government continues to eradicate TB. The purpose of this community service is for families and communities to be able to carry out 5 family health tasks, including recognizing health problems about pulmonary TB, making the right decisions, carrying out treatment procedures, modifying the environment that supports healing, and using health facilities in efforts to cure pulmonary TB patients. The method is to provide education and training to families and communities about the care, treatment, and prevention of pulmonary TB and the formation of the Community TB Care Group. The results obtained showed significant changes in the ability of families and communities to carry out family and community health tasks. Increased ability to recognize pulmonary TB health problems, be able to make decisions, be able to provide care to patients, and be able to modify the environment that supports healing, and all patients have utilized the available health facilities. A TB care group was formed under the name of the TB Care Community Group (KMP TB) "Sehat Paru" in Mandiangin Barat Village. Target Partners are expected to be more proactive in finding new and old cases of pulmonary TB and can also help families to carry out treatment and participate in supervising patients to comply with taking medication regularly. Keywords: Pulmonary TB, family health tasks, care, treatment, prevention